Ethnopsychiatry Nursing as a Transformative Paradigm: Enhancing Equity and Patient-Centered Care in Mental Health - Anggun Novia Indah Fitri; Indi Dwi Shofi Yanti; Fatma Lutfiyatus Sayyida (Tarqabin Nusantara Group, 2025)
Ethnopsychiatry nursing plays a critical role in addressing the mental health needs of culturally diverse populations, including immigrants, refugees, and ethnic minorities. As globalization and migration reshape societies, integrating cultural sensitivity into psychiatric nursing has become essential for equitable and effective care. This systematic literature review synthesizes evidence on cultural considerations in ethnopsychiatry nursing, focusing on five core dimensions: cultural competence, equitable service provision, cultural mediation, social determinants of health, and communication strategies. Drawing on theoretical frameworks such as Campinha-Bacote’s Model of Cultural Competence and Leininger’s Transcultural Nursing Theory, this study highlights the importance of continuous education, institutional support, and culturally validated tools like the DSM-5 Cultural Formulation Interview (CFI) in enhancing diagnostic accuracy and treatment planning. The findings also emphasize the need to address systemic barriers such as language disparities, socioeconomic inequities, and limited access to mental health services. Strategies including interpreter services, community-based outreach, and cultural brokerage models are shown to improve patient engagement and outcomes. Furthermore, recognizing the influence of ecological and multispecies ethnography approaches expands understanding of how environmental and social contexts shape mental well-being. This review underscores that embedding cultural responsiveness into clinical practice, nursing education, and healthcare policies is vital to fostering trust, equity, and inclusivity in mental health care systems. Ultimately, ethnopsychiatry nursing represents a transformative paradigm shift toward more compassionate, patient-centered, and holistic mental health care.